Treatment of domestic greywater using fly ash as an adsorbent incorporated in a slow sand filtration system. Issue 5 (6th May 2022) - Siwila, Stephen; Kapesa, Emmanuel
Abstract: This study investigated the use of fly ash for treatment of domestic greywater when incorporated in a small-scale slow sand filtration (SSF) system. The system was designed, constructed, and tested for treating domestic grey water for irrigation purposes. Configuration A of the system contained sand and gravel only, while configuration B contained fly ash, sand, and gravel. The greywater samples used to test the designed system were collected from the student hostels at the Copperbelt University in Zambia. Additionally, physical and chemical characterisation of the fly ash was done and all key characteristics are presented under the results and discussion section. The system that contained fly ash considerably improved the greywater quality for irrigation purposes by reducing turbidity by 95%, colour by 98%, and chloride by 49% and increasing dissolved oxygen by 33%. However, pH, total dissolved solids, and electrical conductivity were observed to be slightly higher in the treated greywater effluent. The slight increase in these parameters is suspected to have been caused by possible leaching from the the fly ash. Therefore, obtaining fly ash from sources that may not cause any increase in the said parameters in the treated effluent is recommended to maintain compliance with irrigation water quality. HIGHLIGHTS: Very few domestic greywater treatment studies have been done in developing countries, particularly in Zambia. The study presents a low-cost and appropriate technology for low-load domestic greywater treatment in developing countries. Incorporation of fly ash in a small-scale slow sand filtration system is unique and presents both a greywater treatment solution and valuable reuse of fly ash, a solid waste material. Graphical Abstract